2008
DOI: 10.1016/j.expneurol.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

CNS injury, glial scars, and inflammation: Inhibitory extracellular matrices and regeneration failure

Abstract: Spinal cord and brain injuries lead to complex cellular and molecular interactions within the central nervous system in an attempt to repair the initial tissue damage. Many studies have illustrated the importance of the glial cell response to injury, and the influences of inflammation and wound healing processes on the overall morbidity and permanent disability that result. The abortive attempts of neuronal regeneration after spinal cord injury are influenced by inflammatory cell activation, reactive astroglio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
663
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 878 publications
(682 citation statements)
references
References 122 publications
9
663
1
9
Order By: Relevance
“…T he injured CNS is highly inhibitory for axon regeneration, severely limiting functional recovery (1). This results in part from axon regeneration inhibitors (ARIs) that accumulate at injury sites, including molecules on residual myelin [i.e., myelinassociated glycoprotein (MAG), NogoA, and oligodendrocytemyelin glycoprotein) and chondroitin sulfate proteoglycans on astrocytes in the glial scar (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…T he injured CNS is highly inhibitory for axon regeneration, severely limiting functional recovery (1). This results in part from axon regeneration inhibitors (ARIs) that accumulate at injury sites, including molecules on residual myelin [i.e., myelinassociated glycoprotein (MAG), NogoA, and oligodendrocytemyelin glycoprotein) and chondroitin sulfate proteoglycans on astrocytes in the glial scar (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…14 Neutrophils are the main inflammatory cells in acute immune inflammatory reactions. MPO is a specific enzyme present in large quantities in azurophilic granules of neutrophils, contributing to its oxygen-dependent bactericidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…It had been shown that components of the glial scar might interact with ECM molecules [26] via numerous receptors [82][83][84], such as neurocan [85], PTPσR [86,87], CSPGs [87][88][89] etc., preventing axonal regeneration [26]. Particularly, an interaction between astrocytes and CSPGs inhibits regeneration abilities [5].…”
Section: а Bmentioning
confidence: 99%
“…The remodeling of ECM had been demonstrated to take place after brain traumas and in the development of neurodegenerative disorders and in epilepsy. Transgenic animals lacking or having a deficient ECM structure tend to develop an epileptiform activity and characteristic changes of Mossy fibers and granule cells functioning [2,22,23], and astrogliosis [2,[24][25][26]. Additionally, ECM molecular net mechanically restricts diffusion of molecules in the extracellular space [27,28], diffusion of ions and lateral diffusion of receptors in the cell membrane [29,30].…”
Section: Introduction the Brain Extracellular Matrix (Ecm)mentioning
confidence: 99%